Cyclic pushover analysis of steel columns using rigid body spring-discrete element method - Musico, John Kenneth B.
In order to provide plans for retrofitting and improvement of the design of steel structure, there is a need to develop an accurate model that can represent the behavior of steel structures against seismic loading. Columns, which are critical load-carrying members of structure, should be modeled first. Instead of the finite element method (FEM), this study will use the Rigid Body Spring - Discrete Element Method (RBS-DEM), which divides an object into a finite number of rigid body elements mutually connected by spring systems. The hinge model of I-shaped steel columns was based on the section's flexural behavior simplified into a bilinear curve. It is composed of twelve elastoplastic springs-four in longitudinal and eight in diagonal orientation, two shear springs on both lateral directions, and one axial spring in the middle. The RBS-DEM model, after being subjected to monotonic loading, was able to approximately simulate the experimental monotonic behavior of the steel specimens, reacting their corresponding capacities with relatively little deviations. Multi-component models approached the actual flexibility of the column. However, the spring parameters still need to be properly distributed among the different levels of hinges. The load-displacement curves of the model, after being subjected to an increasing sinusoidal load, exhibited correct theoretical behavior except strength degradation because of the lack of hysteresis rules applied to the springs.